2021
DOI: 10.3389/fmed.2021.667543
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA Methylation Regulator YTHDF1 Correlated With Immune Microenvironment Predicts Clinical Outcomes and Therapeutic Efficacy in Breast Cancer

Abstract: Objective: Increasing evidence highlights the roles of N6-methyladenosine (m6A) and its regulators in oncogenesis. Herein, this study observed the associations of m6A regulators with breast cancer.Methods: RNA-seq profiles of breast cancer were retrieved from the Cancer Genome Atlas (TCGA) database. The expression of m6A regulators was analyzed in tumor and normal tissues. Their expression correlations were analyzed by Spearson test. Overall survival (OS) analysis of these regulators was then presented. Gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…However, the relevance of METTL16 and ZC3H13 in cervical cancer is still not fully known. Recent studies have also focused on immune-related prognostic features associated with cancer immune invasion (36). For example, a growing body of literature strongly suggested that YTHDF1 may regulate the immune microenvironment of breast cancer, influencing tumor growth as well as immunotherapy efficacy (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relevance of METTL16 and ZC3H13 in cervical cancer is still not fully known. Recent studies have also focused on immune-related prognostic features associated with cancer immune invasion (36). For example, a growing body of literature strongly suggested that YTHDF1 may regulate the immune microenvironment of breast cancer, influencing tumor growth as well as immunotherapy efficacy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also focused on immune-related prognostic features associated with cancer immune invasion (36). For example, a growing body of literature strongly suggested that YTHDF1 may regulate the immune microenvironment of breast cancer, influencing tumor growth as well as immunotherapy efficacy (36). According to a recent study, YTHDF1 and YTHDF2 induced inflammation in the TIME in non-small-cell lung cancer (37).…”
Section: Discussionmentioning
confidence: 99%
“…The changes of TIME play a signi cant role in the progression of LUAD (51,52). YTHDF1, as a m6A modi cation regulator gene, plays a signi cant role in immune regulation of various cancers (53)(54)(55). In this study, the group with low expression of YTHDF1 had higher in ltration levels of activated B cell, activated dendritic cell, eosinophil, immature B cell, T follicular helper cell, immature dendritic cell, macrophage, mast cell, type 1 T helper cell, monocyte, plasmacytoid dendritic cell and type 17 T helper cell.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma patients treated with anti-PD-1 therapy benefited from ALKBH5 deletion [ 106 ]. Furthermore, the latest research found that a large number of immune checkpoint receptors (including PD-1, TIM-3, and CTLA-4) as well as lymphocytes infiltrating (such as B cells, T cells, macrophages, and dendritic cells) positively correlated with the level of m 6 A readers YTHDF1, and YTHDF2 in respective cancer type, including glioma, NSCLC, kidney renal clean cell carcinoma and BC [ 107 110 ]. Despite the different TIME among tumor types and individual responses, correcting m 6 A regulator disorder was a feasible strategy for cancer immunotherapy (Fig.…”
Section: Mechanisms Of M 6 A-mediated Drug Resistancementioning
confidence: 99%